Assessment of methane emissions and energy recovery potential from the municipal solid waste landfills of Delhi, India. (January 2019) - Ghosh, Pooja; Shah, Goldy; Chandra, Ram; Sahota, Shivali; Kumar, Himanshu; Vijay, Virendra Kumar; Thakur, Indu Shekhar
Graphical abstract: Highlights: Unscientific MSW disposal leads to methane emissions from the landfill sites. Landfill methane emissions for Delhi were estimated using different models. Energy recovery potential from the landfill methane was calculated. Capturing landfill methane was found to be a sustainable waste management option. Abstract: Rising rate of MSW generation and unscientific disposal in the open dumping sites are responsible for emission of high concentrations of methane in developing countries. IPCC Default method (DM), First-order decay (FOD) and LandGEM were used to estimate methane emissions from the unengineered landfill sites of Delhi-Okhla, Bhalswa and Ghazipur between 1984 and 2015. During the period, the total CH4 emissions was found to be 1288.99, 311.18, 779.32 Gg from the 3 landfill sites of Delhi as predicted by DM, FOD and LandGEM respectively. The energy generation potential from methane for the year 2015 was found to vary from 4.16 × 10 8 to 9.86 × 10 8 MJ for Ghazipur, 2.08 × 10 8 to 4.06 × 10 8 MJ for Okhla and 3.42 × 10 8 to 8.11 × 10 8 MJ for Bhalswa. Efficient utilization of methane from the landfills as an energy source can be a sustainable waste management option.